Pengembangan Budaya Literasi melalui Pojok Baca di SMPN 55 Merangin, Jambi - Elintia Hanifah; Candika Candika; Reni Kusmiarti; Ajat Manjato (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The reading corner is a school literacy cultural activity carried out by students in their spare time between class hours to read books available on the shelves in the reading corner. Reading is an important activity in the teaching and learning process, because reading is the ability to absorb knowledge through text or reading material. This reading corner activity itself is carried out as an effort to increase students' reading interest which is applied as a habit. And aims to develop a literacy culture in schools through reading corner activities made in the library. The reading corner activity that was created in the library was carried out with the students of SMPN 55 Merangin aimed at restoring the role of the library as a center for empowering students to develop literacy-based potential. This service is carried out through preparation, socialization of reading corners in libraries, and implementation of reading corners. The result of the dedication to the formation of a reading corner at SMPN 55 Merangin. It is hoped that the establishment of this reading corner can improve school literacy culture.